The Destinies of Africans in the Modern World are Hindered by Selfish Leaders - Ezeogamba, Anthony, Ikechukwu (My University, 2019)
Africa as a nation stands out as one of the cradles of life and civilization but when one looks around today one discovers that Africa has become the dumping ground of used products from Europe and America and to save life, one must travel to get adequate medical attention. Hospitals, schools, road networks, modern mass communication equipments, job opportunities, scholarship schemes, electricity are majorly in shambles or epileptic. When one visits some institutions of higher learning as well as hospitals outside the shores of Africa, one discovers that experts in various fields working in them are from Africa. One of the things migration of the young from Africa to Europe and America has taught us is that African children can compete favourably with their European and American counterparts when placed under the same condition. Hence, it is not that Africans are not gifted intellectually, they are but African's intellectual prowess has not been adequately harnessed as a result of the actions and inactions of their leaders. This proves that there is nothing wrong with African soil, water, air and vegetation. The problem is actually perpetuated daily by old, selfish, visionless and uncharismatic leaders in Africa. When such leaders are on seat, the destinies of their citizens are daily suppressed knowingly or unknowingly. This study aims at showing that African underdevelopment lies in the hands of selfish and sit-tight leaders. Jesus in the above chapter and verses of Matthew urges that anyone who will present himself to be a leader must be the servant of others. The desire of a servant leader centers on how to help all citizens realize their destinies. This study adopted the historical critical exegesis as well as library research as her methodology to arrive at her conclusions. This study argues that if present crop of leaders in Africa were to be selfless and charismatic, Africa will be the envy of the whole world. Significantly, this study will be of immense benefit to Africans and indeed the whole world.
Keywords: Destiny; Leader; Selfish